KINERJA KARYAWAN DITINJAU DARI EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI DAN KOMPLEKSITAS TUGAS DI YAYASAN TRIATMA SURYA JAYA - Tiara Kusuma Dewi; Kukuh Rian Setiawan (UNHI Press, 2022)
This study aims to determine employee performance in terms of the effectiveness of the application of accounting information systems and the complexity of tasks at the Triatma Surya Jaya Foundation. The output target to be achieved is being able to produce scientific papers published in accredited national journals and can be used as references in the development of teaching materials. The analysis technique used in this research is multiple linear regression. Prior to the analysis using the model, the instrument test and classical assumption test were first carried out as a prerequisite for the regression test. The population of this research is the entire financial team of the Triatma Surya Jaya Foundation. The sample used in this study was selected using purposive sampling using the criteria of employees who already use accounting information systems. The results show that partially the application of accounting information systems has a positive effect on employee performance, while its composition has a negative effect on employee performance, but simultaneously the application of accounting information systems affects employee performance in the Triatma Surya Jaya Foundation.